Inheritance of resistance to common bacterial blight in four selected common bean (Phaseolus vulgaris L.) genotypes - Alladassi, Boris M.E.; Nkalubo, Stanley T.; Mukankusi, Clare Mugisha; Mwale, Eric S.; Gibson, Paul; Edema, Richard; Urrea, Carlos A.; Kelly, James D.; Rubaihayo, P.R. (Academic Journals, 2017)
Common bacterial blight (CBB) is the most serious bacterial disease of common bean in Uganda. It causes severe yield losses of up to 62%. Genetic resistance is the most effective option for controlling CBB in smallholder common bean production systems. This study was carried out to determine the inheritance pattern of CBB resistance in leaf and pod of four new resistance sources. The four resistant and four susceptible genotypes were crossed in a half-diallel mating design. F1 individuals were advanced to F2 and evaluated with the parents, in a randomized complete block design replicated twice. Combining ability analysis was performed according to Griffing's (1956) method IV and model 1 using Genstat 12th. General combining ability effects were significant whereas specific combining ability was not suggesting that resistance to CBB in leaf and pod was primarily controlled by additive genes effects. The estimated narrow sense coefficient of genetic determination was moderately high (0.65) for the resistance in leaf and high (0.83) for resistance in pod suggesting that early-generation selection would be effective. Baker’s ratio estimates were relatively high for resistance in leaf (0.79) and pod (0.9) suggesting that hybrids’ performance can be predicted based on the parents’ general combining ability (GCA) effects.